2020
DOI: 10.7759/cureus.11841
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatremia in Diabetic Ketoacidosis: Rare Presentation and a Cautionary Tale

Abstract: Ibarra et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The appearance of hypernatremia in DKA can be attributed to a fluid imbalance. As significant volumes of free fluid are lost (most commonly by polyuria), electrolyte loss (through vomiting and diarrhea) may lag behind, leading to a very unusual occurrence of hypernatremia with osmolytic imbalance[ 4 ]. Although such cases of DKA-induced hypernatremia are infrequent, a 2019 paper reviews the cases of two female patients found to be suffering from hypernatremia secondary to DKA after complaints of altered mental status and other symptoms[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of hypernatremia in DKA can be attributed to a fluid imbalance. As significant volumes of free fluid are lost (most commonly by polyuria), electrolyte loss (through vomiting and diarrhea) may lag behind, leading to a very unusual occurrence of hypernatremia with osmolytic imbalance[ 4 ]. Although such cases of DKA-induced hypernatremia are infrequent, a 2019 paper reviews the cases of two female patients found to be suffering from hypernatremia secondary to DKA after complaints of altered mental status and other symptoms[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While poor intake and deconditioning from an infection likely played a role, it is still uncommon for a DKA patient to present with hypernatremia. The proposed mechanism for hypernatremia in DKA emanates from excessive osmotic diuresis that leads to a volume-depleted state [ 8 ]. The patient’s home regimen included hydrochlorothiazide.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with new-onset diabetes were more likely to have hypernatremia than those who were previously known to be diabetic [ 9 ]. It has been proposed that prolonged DKA eventually leads to loss of hypotonic urine with increased glomerular filtration rate [ 8 , 9 ]. In pediatric populations, the presence of hypernatremia in DKA has been associated with the ingestion of carbohydrate-rich soft drinks [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our lactate sensing scheme is generalizable to additional oxidases and their corresponding analytes including glucose and alcohol. , The addition of these analytes can broaden the applicability of the MSF to other medical conditions. For example, continuous monitoring of sodium, pH, lactate, oxygen, and glucose in individuals experiencing diabetic ketoacidosis can diagnose dehydration (loss of sodium), ketoacidosis (high glucose and low pH), and ischemia (low oxygen and high lactate), directing healthcare professionals toward a specific mode of intervention. An expanded MSF could also be applicable beyond the medical field, such as in bioreactors for protein expression, agriculture, water management, and food industry, where sensing pH, glucose, and sodium would provide vital information to each respective field. …”
Section: Discussionmentioning
confidence: 99%